Theoretical and methodological principles of classification of functional failures of buildings and their structural elements during theoretical inspection - DEMYDOVA, Olena; MILITSKYI, Kostiantyn (Ways to Improve Construction Efficiency, 2025)
The article explores the theoretical and methodological principles of ensuring the operational reliability of buildings through the implementation of the concept of functional failure of buildings or their structural systems. The relevance of the work is due to the need to modernize the tools for technical inspection of objects that have been exposed to unforeseen impacts as a result of hostilities, where the nature of the loads significantly deviates from standard design scenarios. The article emphasizes the importance of transitioning to a systematic analysis of physical failure mechanisms. The purpose of the study is to scientifically substantiate and systematize the types of functional failures of load-bearing structures using a more expanded approach. In the work, functional failure is considered as a state in which the structure loses its ability to meet design requirements and tolerances, even if a satisfactory visual condition is maintained. The scientific novelty lies in the development of a comprehensive classification based on the analysis of the technological nature, causes of occurrence, rate of degradation and the scale of the consequences of failures. The analysis of the technological nature allowed us to distinguish the levels of degradation: from the initial deterioration of operational parameters to the occurrence of excessive deformations and critical loss of bearing capacity. Special attention was paid to the separation and expansion of internal factors associated with design and technological errors and external factors caused by extreme mechanical loads and blast waves. It was proven that the speed of the system's transition to a failure state determines the model of further monitoring, where gradual processes allow for preventive measures, and sudden failures require specific methods of instant diagnostics. Classification by consequences allows us to assess the degree of risk for operation, distinguishing between local defects, limitations in performance and complete systemic destabilization caused by a chain reaction of loss of stability of key load-bearing structures. The practical significance of the results lies in creating a theoretical basis for increasing the objectivity of expert conclusions and predicting the residual bearing capacity of structures. The proposed typification serves as a foundation for choosing sound strategies for the restoration, strengthening or dismantling of objects in the process of post-war reconstruction of Ukraine. A systematic approach to classification allows us to take into account not only visual damage, but also the gradual deterioration of structural integrity, ensuring the mechanical safety of construction objects in the post-war period.